Personality Traits and Their Relationship with Some Demographic Variables Among University Students According to the Big Five Personality Traits Model- A Field Study at the University of Algiers 2 - Zerrouti, Asma; Sahraoui, Wafia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aimed to investigate personality traits and their relationship with certain demographic variables among university students, based on the Five-Factor Model of Personality, through a field study at the University of Algiers 2. The study employed a descriptive-analytical methodology to explore differences in personality traits according to demographic factors. The sample consisted of 50 students selected through a random sampling method. Data were collected using the Costa and McCrae (1992) questionnaire to assess the five personality traits. The hypotheses were tested using statistical methods including means, standard deviations, frequencies, t-tests, and ANOVA to examine differences between groups. The results revealed statistically significant differences in personality traits according to the Five-Factor Model. Gender showed a notable effect, with males scoring higher in some traits. Additionally, cultural environment differences were observed, favoring students residing in northern provinces, indicating that social and cultural factors influence the development of personality traits in university students. These findings underscore the importance of considering demographic characteristics when studying personality in academic settings.